Pro SharePoint 2010 disaster recovery and high availability - Cummins, Stephen (Apress, 2011)
Few IT professionals take the time to learn what needs to be known to do disaster recovery well. Most labor under the pretense that good administration equals close to five-nines uptime. Most technical people do not see the value of planning for disasters until the unexpected has already happened, and the effects of a disaster involving a SharePoint farm which today houses business information, line-of-business applications, sensitive information, extranets, and other highly important assets can be staggering. Pro SharePoint 2010 Disaster Recovery and High Availability will take you through a step-by-step process to show how to build an awareness and reaction plan for the inevitable. With a focus on real-world experiences and war stories, author Stephen Cummins weaves an expert tale of woe response and offers you: Ways to see the warning signs of disaster, and ways to avoid it Ways to respond to a disaster while it is happening Perhaps most importantly, how to develop a plan to deal with disaster when it inevitably does happen